Personalised information retrieval through the use of a collaboration awareness tool, a chat and a forum tool in a computer supported collaborative learning task. (12th December 2011) - Lambropoulos, Niki; Romero, Margarida
In recent years, Computer Supported Collaborative Learning (CSCL) has expanded in higher education, both in face to face and online universities. Considering the organisation challenge the students face in CSCL, there is a need for developing computer supported tools to support the students' organisation activity. In this study, we consider the personalised information retrieval in a CSCL task through the use of a Group-Awareness widget (GAw), called EuroCAT. The GAw EuroCAT supports the students' declaration of personal information and their display to the teammates. We aim to analyse the comparative use of the collaboration tools available for the students in the CSCL task comparing the use of GAw EuroCAT allowing to retrieve personalised information and traditional communication tools such as the forum and the chat. A quasi-experimental situation was conducted on psychology undergraduate students. The results showed a higher organisational and knowledge convergence in the group of students using EuroCAT.